A 3-min weighted vests re-warmups induce sprint performance enhancements at the start of the second half of a soccer match-play - Ltifi, Mohamed Amine; Turki, Olfa; Racil, Ghazi; Larion, Alin; Chelly, Mohamed Souhaiel; Ben Saad, Helmi; Khalifa, Riadh; Chamari, Karim; Padulo, Johnny (Frontiers in Physiology, 2023)
Purpose. This study aimed to investigate the effect of 3-min weighted vests re-warm-ups (RWUP) on 20-m sprint performance after the break. Methods. Using a randomized, and counterbalanced cross-over design, twenty U15 elite soccer players performed four RWUP trials which consisted of 15-min of passive rest (control: CONT), 3×15m sprint (RW0%), sprinting with a vest-loaded at 5% of body-mass (BM) (RW5%), sprinting with a 10% BM vest. The 3-min RWUP protocols started 10-min after the commencement of the 15-min between-halves break and concluded 2-min before its end. During each testing session, the subject’s RPE scores, and 20-m sprint performance were registered before the first half, and at the end of the break of the simulated match-play. Results. Both RW5% and RW10% showed better 20-m sprint performance (2.94±0.21/2.94±0.13s) compared with RW0% (p=0.002/0.006) and CONT (p=0.001), respectively. However RW5% was found to be the best RWUP option as it has induced lower RPE scores (3.95±0.72 a.u.), compared with RW10% (5.10±1.11a.u) with p=0.0001. Conclusions. RWUP consisting of 3 series of 15-m sprint with vests loaded at 5%, or 10% of BM induce 20-m sprint enhancements 15 min post first half of match-play.